Analytical procedure for total mercury determination in fishes and shrimps by chronopotentiometric stripping analysis at gold film electrodes after microwave digestion - Augelli, M. A.; Munoz, R. A. A.; Richter, E. M.; Cantagallo, M. I.; Angnes, L. (Elsevier B.V., 2007)
A method for the total mercury determination in fish and shrimps employing chronopotentiometric stripping analysis on gold film electrodes is described. Fish and shrimp tissues were digested using a microwave oven equipped with closed vessels. We developed a microwave heating program which decomposed all the samples employing diluted nitric acid and hydrogen peroxide. The proposed method was validated by analyzing a certified reference material and then applied for different fish species from fresh water and seawater acquired in local markets of São Paulo city, Brazil. The Brazilian legislation establishes 0.5 and 1 mg per kilogram of fish as upper limit of mercury for omnivorous and predator species, respectively. Except for blue shark tissues, the mercury content was situated below 0.5 mu g g(-1) for all the analyzed samples. The detection limit of the proposed method was calculated as 5 ng g(-1) of sample utilizing 5 minutes of electrodeposition (+300 mV vs. Ag/AgCl) on the gold electrode. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: mercury; fish; shrimp; microwave digestion; chronopotentiometric stripping analysis; gold electrodes